The Role of Self-Efficacy in Mediating Entrepreneurship Education and Learning Experiences on Entrepreneurial Intention - Maha Putra; Suryana; Hari Mulyadi; Suwatno; Maha Putra (Universitas Pendidikan Ganesha, 2026)
Although entrepreneurship education has been widely integrated into higher education, students’ entrepreneurial intention levels remain relatively low. This study aims to analyze the mediating role of self-efficacy in the relationship between entrepreneurship education, learning experiences, and entrepreneurial intentions among university students. This study employed a quantitative design with a descriptive-correlational approach and a cross-sectional method. The research population consisted of 380 undergraduate students. Data were collected through structured online questionnaires. The research instruments measured the variables of entrepreneurship education, learning experiences, self-efficacy, and entrepreneurial intentions using a five-point Likert scale. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results showed that entrepreneurship education and learning experiences had a direct and significant effect on both self-efficacy and entrepreneurial intentions. Self-efficacy was also found to have a direct and significant influence on entrepreneurial intentions and to serve as a significant mediator in the relationship between entrepreneurship education and entrepreneurial intentions, as well as between learning experiences and entrepreneurial intentions. Based on these findings, this study concludes that entrepreneurship education should not merely focus on knowledge transfer, but should also emphasize experiential, reflective, and practical learning that can systematically strengthen students’ self-efficacy. The results of this study have important implications for higher education institutions and policymakers in designing more effective entrepreneurship programs to foster students’ entrepreneurial intentions.